2000
DOI: 10.1097/00124645-200003000-00009
|View full text |Cite
|
Sign up to set email alerts
|

From School to Work: Employer Perceptions of Nursing Skills

Abstract: Questions periodically arise regarding clinical competencies and students' ability to perform in the employment setting after graduating from a baccalaureate nursing (BSN) program. This article describes a collaborative project between a nurse administrator in an acute care facility and a nurse educator in a baccalaureate nursing program. The project was designed to evaluate whether expected competencies of BSN graduates were evident in the work setting. Skills and behaviors of BSN graduates were evaluated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…2,5,13 In addition, the field of health-related sciences continues rapid development of new knowledge and computerized technology supporting patient care. 14 To provide a wide range of options for student learning resembling real-life practice without compromising patient care, innovative teaching strategies need to be explored and used.…”
Section: Nursing Students and Learning In Clinical Practicementioning
confidence: 99%
“…2,5,13 In addition, the field of health-related sciences continues rapid development of new knowledge and computerized technology supporting patient care. 14 To provide a wide range of options for student learning resembling real-life practice without compromising patient care, innovative teaching strategies need to be explored and used.…”
Section: Nursing Students and Learning In Clinical Practicementioning
confidence: 99%
“…Previous descriptive work 10,13,18,19 has shown that managing the care of multiple patients, making decisions about clinical priorities, and communicating with others in the care setting were areas in which new baccalaureate graduates express difficulty. Previous descriptive work 10,13,18,19 has shown that managing the care of multiple patients, making decisions about clinical priorities, and communicating with others in the care setting were areas in which new baccalaureate graduates express difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…This means that it is preferable–in the absence of a full-time school nurse in every building every day–to hire bachelor’s prepared nurses rather than sacrificing quality with personnel who have technical or educational requirements less than those that would be obtained from a baccalaureate degree in nursing. Multiple research studies have shown that “baccalaureate graduates tend to be more self-directed and independent and more proficient in use of research, leadership, theoretical, conceptual, and psychosocial assessment skills” (Lowry, Timms, & Underwood, 2000, p. 81; National Advisory Council on Nurse Education and Practice [NACNEP], 2010; Ellenbecker, 2010). Ultimately, this will produce better health and academic outcomes.…”
Section: Addressing the Issuementioning
confidence: 99%